The Role of Strategic Direction in the Quality of Educational Services in Yemeni Private Universities - Almahdi, Abdulrahman Ahmed Mohammed; Al-Manzuoa, Zayed Ali AbdulKhaleq (Journal of Posthumanism, 2025)
The study examined the role of strategic orientation on the quality of educational services in Yemeni private universities. The study used a descriptive-analytical approach and a questionnaire as a tool to collect information from the study sample, which comprised (297) academic and administrative leaders at private universities in Sana’a.The results demonstrated a role for strategic orientation, with its dimensions (university vision, university mission, university objectives, and university organizational values), in the quality of educational services in Yemeni private universities. It also demonstrated that the best model for measuring the impact of the dimensions of strategic orientation on the quality of educational services in Yemeni private universities is the model that includes the dimensions (university vision, university objectives, and university organizational values).